2010
DOI: 10.3390/nu2030299
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 in Health and Disease

Abstract: Vitamin B12 is essential for DNA synthesis and for cellular energy production.This review aims to outline the metabolism of vitamin B12, and to evaluate the causes and consequences of sub-clinical vitamin B12 deficiency. Vitamin B12 deficiency is common, mainly due to limited dietary intake of animal foods or malabsorption of the vitamin. Vegetarians are at risk of vitamin B12 deficiency as are other groups with low intakes of animal foods or those with restrictive dietary patterns. Malabsorption of vitamin B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
293
1
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(313 citation statements)
references
References 94 publications
2
293
1
17
Order By: Relevance
“…Similarly to their results, in the present study we found decreased vitamin B 12 levels in our T2D-CKD patients regardless of the CKD stage, although the concentrations found in our population were not an expression of vitamin B 12 deficiency, in which plasma levels are below 200 pg/ml. The finding that at stage IV the vitamin B 12 levels are significantly higher than in other stages of CKD is probably due to the reduced renal function in those patients, as it was demonstrated that excessive vitamin B 12 is normally excreted in the urine [24]. We also found that folate levels were comparable to those of controls in our T2D-CKD patients.…”
supporting
confidence: 73%
“…Similarly to their results, in the present study we found decreased vitamin B 12 levels in our T2D-CKD patients regardless of the CKD stage, although the concentrations found in our population were not an expression of vitamin B 12 deficiency, in which plasma levels are below 200 pg/ml. The finding that at stage IV the vitamin B 12 levels are significantly higher than in other stages of CKD is probably due to the reduced renal function in those patients, as it was demonstrated that excessive vitamin B 12 is normally excreted in the urine [24]. We also found that folate levels were comparable to those of controls in our T2D-CKD patients.…”
supporting
confidence: 73%
“…Parietal cells in the stomach secrete both hydrochloric acid and the vitamin B-12-binding protein IF, and low IF concentrations impair vitamin B-12 absorption. Insufficient IF is caused by pernicious anemia, an autoimmune disease, which typically presents as megaloblastic anemia (20)(21)(22). IF-bound vitamin B-12 is absorbed primarily in the ileum by the cubulin FIGURE 1 Vitamin B-12 in 1-carbon metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, long-term effects of FGR include growth retardation (Chia and Huang, 2014), developmental anomalies (Streimish et al, 2012), congenital anomalies (Clausson et al, 1999), cardiovascular diseases (Khadilkar and Parthasarathy, 2015), ischemia anoxic encephalopathy (Kovo et al, 2015), chronic lung diseases (Bose et al, 2009), gastrointestinal diseases (Liu et al, 2014), kidney diseases (Ojeda et al, 2008), and endocrine metabolic disorders (Sánchez-Vera et al, 2005). Folic acid (FA) (Walter et al, 2016) and Vitamin B12 (Vit B12) (O'Leary and Samman, 2010) are mainly obtained through diet, and are important coenzymes for DNA synthesis. The fetus requires high levels of FA and Vit B12, especially during late pregnancy.…”
Section: Introductionmentioning
confidence: 99%